A Novel Green Synthesis of Thalidomide and Analogs - Ellis Benjamin (18891907) (2017)
Thalidomide and its derivatives are currently under investigation for their antiangiogenic, immunomodulative, and anticancer properties. Current methods used to synthesize these compounds involve multiple steps and extensive workup procedures. Described herein is an efficient microwave irradiation green synthesis method that allows preparation of thalidomide and its analogs in a one-pot multicomponent synthesis system. The multicomponent synthesis system developed involves an array of cyclic anhydrides, glutamic acid, and ammonium chloride in the presence of catalytic amounts of 4-N,N-dimethylaminopyridine (DMAP) to produce thalidomide and structurally related compounds within minutes in good isolated yields. Other Information Published in: Journal of Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2017/6436185